Optimized Colorectal Cancer Patients’ Management During the COVID-19 Pandemic: Triage and Treatment - Pengcheng Xiang; Junyi Han; Tiffany I. Leung; Naomi I. Maria; Zitian Xiao; Xiuhao Zhao; Zhijin Zhang; Shaohua Qu; Ewelina Biskup (healthbook TIMES. Oncology Hematology)
# Background